Regulation of Dendritic Spine Motility in Cultured Hippocampal Neurons - Korkotian, Eduard (J Neurosci, 2001)
Regulation of dendritic spine motility was studied in dissociated cultures of the rat and mouse hippocampus, using green fluorescent protein-labeled neurons or neurons loaded with the calcium-sensitive dye Oregon Green-1. Cells were time-lapse-photographed on a confocal laser-scanning microscope at high resolution to detect movements as well as spontaneous fluctuations of intracellular calcium concentrations in their dendritic spines. Active presynaptic terminals attached to the spines were labeled with FM4-64, which marks a subset of synaptophysin-labeled terminals. Dendritic spines were highly motile in young, 4- to 7-d-old cells. At this age, neurons had little spontaneous calcium fluctuation or FM4-64 labeling. Within 2–3 weeks in culture, dendritic spines were much less motile, they were associated with active presynaptic terminals, and they expressed high rates of spontaneous calcium fluctuations. Irrespective of age, and even on the same dendrite, there was an inverse relationship between spine motility and presence of FM4-64-labeled terminals in contact with the imaged spines. Spine motility was blocked by latrunculin, which prevents actin polymerization, and was disinhibited by blockade of action potential discharges with tetrodotoxin. It is proposed that an active presynaptic terminal restricts motility of dendritic spines.